Strategi Guru PAI dalam Menanamkan Nilai Akhlakul Karimah pada Generasi Z di MTs Sunan Ampel Menampu Kabupaten Jember - Ismaniya, Fais Zhatul; Rofiq, M. Nafiur (DIMAR: Jurnal Pendidikan Islam, 2025)
The rapid development of technology in the digital era presents significant challenges in shaping the character of Generation Z, especially in instilling the values of akhlakul karimah (noble character). This generation is highly familiar with digital tools but often faces moral crises due to media influence and weak environmental supervision. This study aims to analyze the strategies implemented by Islamic Religious Education (PAI) teacher in instilling akhlakul karimah values among Generation Z students at MTs Sunan Ampel Menampu, Jember Regency. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation. The findings indicate that PAI teachers apply several key strategies, including exemplary conduct (uswah hasanah), habituation of religious activities, advice and motivation (mau’idzah), a fair reward and punishment system, and strong collaboration with students’ parents. These strategies are implemented both in classroom learning and through scheduled religious program supported by the integration of technological media. Despite challenges such as students’ lack of discipline and external negative influences, teachers consistently guide students using persuasive approaches and continuous character development. The study reveals a positive transformation in students’ behavior, such as increased discipline, respect, and responsibility, especially in religious and social contexts. In conclusion, the adaptive and collaborative strategies of PAI teachers play a vital role in nurturing Islamic character among Generasi Z. The success off character education rooted in akhlakul karimah depends on strong synergy between schools, families, and the broader community to ensure sustainable and effective moral development in the digital age.